The Impact of Fiscal Decentralization on Welfare in Selected Provinces in Indonesia (Jurnal Bina Praja, 2020)
Human resources have a pivotal role in a country because it determines the growth and development of an economy. In economic terms, factor of production can be defined as labor, land, and capital, thereforethe quality of human resources does matter to determine the growth and development in a country. Since ASEAN Economic Community has already started in 2015 and it put forward competitive conditions among countries, human development has been attracting a lot of interest. Furthermore, poverty is also considered as an interesting topic in Indonesia because it has been 74 years after Indonesian independence, and poverty is still a difficult problem to alleviate. In 2016, Indonesia is recorded as having the second largest number of poor people in ASEAN. Various programs have been implemented by the regional governments including fiscal decentralization. This paper aims to find the impact of fiscal decentralization on welfare. In this article, we focused on human development and poverty to reflect welfare. We use regional government expenditure, regional government revenue, and balancing funds to measure fiscal decentralization in selected provinces in Indonesia-West Java, Central Java, East Java, Special Capital Region of Jakarta, Special Region of Yogyakarta, and Banten. We found decentralization policy statistically significant affects human development and poverty alleviation. Hence, this information can be used to develop targeted interventions aimed on increasing the regional government revenue and reducing unnecessary regional government expenditure to escalate fiscal space. The fiscal space can be used to fund programs that encourage human development and poverty alleviation.
Keywords: Fiscal Decentralization; Public Welfare; Human Development; Poverty Alleviation; Java Island